SnRK2.10 kinase differentially modulates expression of hub WRKY transcription factors genes under salinity and oxidative stress in Arabidopsis thaliana - Rachowka, Julia; Anielska-Mazur, Anna; Bucholc, Maria; Stephenson, Krystyna; Kulik, Anna (Frontiers in Plant Science, 2023)
In nature, all living organisms must continuously sense their surroundings and react to the occurring changes. In the cell, the information about these changes is transmitted to all cellular compartments, including the nucleus, by multiple phosphorylation cascades. Sucrose Non-Fermenting 1 Related Protein Kinases (SnRK2s) are plant-specific enzymes widely distributed across the plant kingdom and key players controlling abscisic acid (ABA)-dependent and ABA-independent signaling pathways in the plant response to osmotic stress and salinity. The main deleterious effects of salinity comprise water deficiency stress, disturbances in ion balance, and the accompanying appearance of oxidative stress. The reactive oxygen species (ROS) generated at the early stages of salt stress are involved in triggering intracellular signaling required for the fast stress response and modulation of gene expression. Here we established in Arabidopsis thaliana that salt stress or induction of ROS accumulation by treatment of plants with H2O2 or methyl viologen (MV) induces the expression of several genes encoding transcription factors (TFs) from the WRKY DNA-Binding Protein (WRKY) family. Their induction by salinity was dependent on SnRK2.10, an ABA non-activated kinase, as it was strongly reduced in snrk2.10 mutants. The effect of ROS was clearly dependent on their source. Following the H2O2 treatment, SnRK2.10 was activated in wild-type (wt) plants and the induction of the WRKY TFs expression was only moderate and was enhanced in snrk2.10 lines. In contrast, MV did not activate SnRK2.10 and the WRKY induction was very strong and was similar in wt and snrk2.10 plants. A bioinformatic analysis indicated that the WRKY33, WRKY40, WRKY46, and WRKY75 transcription factors have a similar target range comprising numerous stress-responsive protein kinases. Our results indicate that the stress-related functioning of SnRK2.10 is fine-tuned by the source and intracellular distribution of ROS and the co-occurrence of other stress factors.